Devir macumbeiro: a epistemologia de terreiro como produtora de conhecimento, de existência e de alteridade no Brasil - Bonine, Eduardo (2024)
This work presents the devir macumbeiro as an autonomous concept to understand and perspective Brazilian way. Based on terreiro epistemology, we will present an exusíaca ethic and an exunouveau aesthetics that are alternatives to hegemonic scientific systematizations. We start from the hypothesis that the terreiros of samba, macumba and suburb are encounters between the cracks of social disputes, therefore, they elaborate and a “macumbeiro body” active in the dynamics of Brazilianness with nation of Brazil. We concluded the thesis reaffirming our hypothesis that it is possible to realize an alternative existence amidst the policies of silencing and extermination of unwanted bodies by the hegemonic State. The “macumbeiro body” is Brazilian way and devir macumbeiro is its rite